THE MEDIATING ROLE OF EMOTIONAL SATISFACTION AND PATIENT TRUST IN THE RELATIONSHIP BETWEEN SERVICE QUALITY AND REVISIT INTENTION - Hasanah, Ratu Ina; Meutia, Meutia; Lutfi, Lutfi (Ridwan Institute, 2024)
Revisit intention is an interesting issue in the field of marketing and is important in the service industry because maintaining customer loyalty in the long term is the success key of a business. Measuring and predicting revisit intention is considered as one of the important indicators of the achievement of service companies. This study aims to investigate the effects of service quality on the revisit intention of patients to hospitals, as well as the mediating role of emotional satisfaction and patient trust on the relationship between service quality and revisit intention. The sample used in this study amounted to 200 respondents who were patients with non BPJS Health insurance who visited at least three times in 2021-2023. The sampling technique in this study used non probability sampling technique (purposive sampling). The method used in this study is Structural Equation Modeling (SEM) and using smart PLS 3.2.9 software. The findings of this study shows that service quality does not have a direct impact on revisit intention of non-BPJS Health patients, but rather an indirect impact through emotional satisfaction and patient trust. Emotional satisfaction mediates the relationship between service quality and revisit intention, while patient trust also plays a role. Based on the analysis of mediation influence, emotional satisfaction and patient trust play a role in full mediation (indirect-only).